2018
DOI: 10.1111/gtc.12579
|View full text |Cite
|
Sign up to set email alerts
|

Hyperactivation of Nrf2 leads to hypoplasia of bone in vivo

Abstract: Keap1 is a negative regulator of Nrf2, a master transcription factor that regulates cytoprotection against oxidative and electrophilic stresses. Although several studies have suggested that the Keap1-Nrf2 system contributes to bone formation besides the maintenance of redox homeostasis, how Nrf2 hyperactivation by Keap1 deficiency affects the bone formation remains to be explored, as the Keap1-null mice are juvenile lethal. To overcome this problem, we used viable Keap1-deficient mice that we have generated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 29 publications
1
26
1
Order By: Relevance
“…So Nrf2 is considered as playing an important role in the regulation of bone homeostasis in bone cells 12 . Recently, two Japanese labs have examined the role of Keap1 in skeletal development and bone homeostasis 13,14 . Because Keap1 −/− mice die within 3 weeks of birth due to severe hyperkeratosis in esophagus and forestomach 15 , one lab examined the newborn Keap1 −/− mice and found that talus and calcaneus bone formation is partially retarded 13 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…So Nrf2 is considered as playing an important role in the regulation of bone homeostasis in bone cells 12 . Recently, two Japanese labs have examined the role of Keap1 in skeletal development and bone homeostasis 13,14 . Because Keap1 −/− mice die within 3 weeks of birth due to severe hyperkeratosis in esophagus and forestomach 15 , one lab examined the newborn Keap1 −/− mice and found that talus and calcaneus bone formation is partially retarded 13 .…”
mentioning
confidence: 99%
“…Because Keap1 −/− mice die within 3 weeks of birth due to severe hyperkeratosis in esophagus and forestomach 15 , one lab examined the newborn Keap1 −/− mice and found that talus and calcaneus bone formation is partially retarded 13 . Because the juvenile death of Keap1 −/− mice is caused by the obstruction of the esophagus and starvation 15 , the other lab generated a viable model by crossing the floxed Nrf2 mice, keratin5-drived-Cre mice and Keap1 −/− mice in which a squamous epithelium-specific Nrf2 deficiency in the context of systemic Keap1 deletion 14,16 . These unique mice (Keap1 −/− ; Nrf2 Flox/Flox ; Keratin5-Cre), which Genotyping.…”
mentioning
confidence: 99%
“…The actions of NRF2 on the skeleton have been examined by several laboratories using mice with global deletion of NRF2 or NRF2 hyperactivation due to deletion of KEAP1. These studies indicate that NRF2 is detrimental to the accrual of bone mass and contributes to bone loss in old male mice . In contrast, NRF2 is required for the accrual of normal bone mass but has no influence on the loss of bone mass in female mice .…”
Section: Mitochondrial Dysfunctionmentioning
confidence: 78%
“…In striking contrast to Keap1 -/animals (18,19), Keap1 hm mice exhibited only mild hyposthenuria and polyuria at baseline and had normal urine concentrating ability and upregulation of plasma renin activity in response to 12-hour water deprivation. Thus, it is possible that Nrf2 activation displays hormesis (28), with activity above a certain threshold causing adverse outcomes (18,19,70).…”
Section: Discussionmentioning
confidence: 99%